Considerations for the Selection of Time-Limited Walk Tests Poststroke: A Systematic Review of Test Protocols and Measurement Properties. Issue 1 (January 2017) - Salbach, Nancy M.; O'Brien, Kelly K.; Brooks, Dina; Irvin, Emma; Martino, Rosemary; Takhar, Pam; Chan, Sylvia; Howe, Jo-Anne
Abstract : Background and Purpose: Systematic reviews of research evidence describing the quality and methods for administering standardized outcome measures are essential to developing recommendations for their clinical application. The purpose of this systematic review was to synthesize the research literature describing test protocols and measurement properties of time-limited walk tests in people poststroke. Methods: Following an electronic search of 7 bibliographic data-bases, 2 authors independently screened titles and abstracts. One author identified eligible articles, and performed quality appraisal and data extraction. Results: Of 12 180 records identified, 43 articles were included. Among 5 walk tests described, the 6-minute walk test (6MWT) was most frequently evaluated (n = 36). Only 5 articles included participants in the acute phase (<1 month) poststroke. Within tests, protocols varied. Walkway length and walking aid, but not turning direction, influenced 6MWT performance. Intraclass correlation coefficients for reliability were 0.68 to 0.71 (12MWT) and 0.80 to 1.00 (2-, 3-, 5- and 6MWT). Minimal detectable change values at the 90% confidence level were 11.4 m (2MWT), 24.4 m (5MWT), and 27.7 to 52.1 m (6MWT; n = 6). Moderate-to-strong correlations (≥0.5) between 6MWT distance and balance, motor function, walking speed, mobility, and stair capacity were consistently observed (n = 33). Moderate-to-strong correlations between 5MWT performance and walking speed/independence (n = 1), and between 12MWT performance and balance, motor function, and walking speed (n = 1) were reported. Discussion and Conclusions: Strong evidence of the reliability and construct validity of using the 6MWT poststroke exists; studies in the acute phase are lacking. Because protocol variations influence performance, a standardized 6MWT protocol poststroke for use across the care continuum is needed. Video Abstract available for more insights from the authors (see Supplemental Digital Content 1, http://links.lww.com/JNPT/A150 ). Abstract : Supplemental Digital Content is Available in the Text.